The case for fencing remains intact. (20th August 2013) - Packer, C.; Swanson, A.; Canney, S.; Loveridge, A.; Garnett, S.; Pfeifer, M.; Burton, A. C.; Bauer, H.; MacNulty, D.; Chase, Jonathan
Abstract Creel et al. argue against the conservation effectiveness of fencing based on a population measure that ignores the importance of top predators to ecosystem processes. Their statistical analyses consider, first, only a subset of fenced reserves and, second, an incomplete examination of 'costs per lion.' Our original conclusions remain unaltered.